MODEL DISCOVERY LEARNING BERBANTUAN MEDIA POSTER BERBASIS CANVA DALAM PEMBELAJARAN MENULIS TEKS DESKRIPSI SISWA KELAS VII MTs MAMBA’UL HUDA - Firda Kholisotul Ummah; Joko Setiyono; Masnuatul Hawa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The descriptive text writing skills of seventh-grade students at MTs Mamba'ul Huda were relatively low. Students experienced difficulties in selecting appropriate vocabulary, constructing descriptive sentences, and describing objects in detail, resulting in writing outcomes that did not meet the minimum learning achievement criteria. This study aimed to improve students' descriptive text writing skills through the implementation of the Discovery Learning model supported by Canva-based poster media. This study employed Classroom Action Research (CAR), conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The participants were 28 seventh-grade students of MTs Mamba'ul Huda in the 2025/2026 academic year. Data were collected through writing tests, observations, interviews, and documentation and analyzed using descriptive quantitative and qualitative techniques. The findings indicated that the implementation of the Discovery Learning model supported by Canva-based poster media improved students' descriptive text writing skills. The mean score increased from 57 in the pre-action stage to 71 in Cycle I and 79 in Cycle II. Learning mastery also improved significantly, from 14% in the pre-action stage to 57% in Cycle I and 82% in Cycle II. In addition, students became more active and motivated during the learning process. Therefore, the implementation of the Discovery Learning model supported by Canva-based poster media effectively improved the descriptive text writing skills of seventh-grade students at MTs Mamba'ul Huda.